2015
DOI: 10.3390/molecules20034071
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Antifungal Activity and QSAR of Some Novel Carboxylic Acid Amides

Abstract: A series of novel aromatic carboxylic acid amides were synthesized and tested for their activities against six phytopathogenic fungi by an in vitro mycelia growth inhibition assay. Most of them displayed moderate to good activity. Among them N-(2-(1H-indazol-1-yl)phenyl)-2-(trifluoromethyl)benzamide (3c) exhibited the highest antifungal activity against Pythium aphanidermatum (EC50 = 16.75 µg/mL) and Rhizoctonia solani (EC50 = 19.19 µg/mL), compared to the reference compound boscalid with EC50 values of 10.68 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 18 publications
0
18
0
1
Order By: Relevance
“…Qin et al [ 88 ] described the synthesis of a novel series of aromatic carboxylic acid amides containing 1 H -indazole moiety based on a bioisosterism approach and evaluation of their activities against six phytopathogenic fungi by an in vitro mycelia growth inhibition assay. The preliminary biological results demonstrated that all of the target molecules displayed moderate to good activity against the six kinds of fungi.…”
Section: Biological Applications Of Indazole Derivativesmentioning
confidence: 99%
“…Qin et al [ 88 ] described the synthesis of a novel series of aromatic carboxylic acid amides containing 1 H -indazole moiety based on a bioisosterism approach and evaluation of their activities against six phytopathogenic fungi by an in vitro mycelia growth inhibition assay. The preliminary biological results demonstrated that all of the target molecules displayed moderate to good activity against the six kinds of fungi.…”
Section: Biological Applications Of Indazole Derivativesmentioning
confidence: 99%
“…The antifungal activity of the synthesized compounds was performed according to previously reported procedures [ 33 ]. The fungicidal activity of the target compounds against R. solani , F. oxysporum , B. cinerea Pers., sunflower sclerotinia rot and rape sclerotinia rot were evaluated using a mycelium growth rate test [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Three-dimensional molecular structures were built using the SKETCH module in Sybyl 7.3, while structural energy minimization was performed with the Tripos force field until a gradient convergence of 0.05 kcal/(mol A) was achieved. Gasteiger–Hückel charges were calculated and used to construct the CoMFA models [20]. …”
Section: Methodsmentioning
confidence: 99%